ANALISIS STRATEGI AMIL DALAM PENGHIMPUNAN DANA ZAKAT MELALUI BAITUL MAAL HIDAYATULLAH - Abdul Wahid Mongkito; Didin Hafidhuddin; Irfan Syauqi Beik (Kasaba, 2019)
This thesis which was completed in April 2014 is about the right strategies for fundraising zaka by LAZNAS BMH. The manager needs strategies to optimize zakat fundraising. Through the study of internal factors and external factors LAZNAS BMH organization, an analysis of Internal and External Factors Evaluation in order to obtain the right strategy to be done by the organization LAZNAS BMH although still common. Further research conducted by TOWS matrix to get some viable strategy undertaken by LAZNAS BMH, choose the best strategy of the proper strategies conducted by LAZNAS BMH with Quantitative Strategy Planning Matrix (QSPM) analysis method. After analyzing QSPM, then there are three strategies that best suit the condition of the Internal and External LAZNAS BMH to optimize the collection of zakat funds are: to socialize so that Muslims are interested in LAZNAS BMH, expanding the scope of the zakat, as well as making zakat fund raising strategies and methods of the target receipt of zakat funds.